2018
DOI: 10.3389/fimmu.2018.01376
|View full text |Cite
|
Sign up to set email alerts
|

More Than Skin Deep: Autophagy Is Vital for Skin Barrier Function

Abstract: The skin is a highly organized first line of defense that stretches up to 1.8 m2 and is home to more than a million commensal bacteria. The microenvironment of skin is driven by factors such as pH, temperature, moisture, sebum level, oxidative stress, diet, resident immune cells, and infectious exposure. The skin has a high turnover of cells as it continually bares itself to environmental stresses. Notwithstanding these limitations, it has devised strategies to adapt as a nutrient-scarce site. To perform its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 234 publications
(254 reference statements)
2
58
0
Order By: Relevance
“…However, UV pretreatment did not inhibit recruitment of macrophages and neutrophils to DNFB-treated Rubcn -/ears, though mast cells were efficiently suppressed by UV exposure in Rubcn -/mice (Fig 3, A). In addition to ubiquitous immune cells, the skin contains specialized resident immune cells (such as CD207 1 CD11c 1 CD11b 1 LCs, CD103 1 CD207 1 CD11c 1 CD11b lo dDC1s and CD301b 1 CD207 lo CD11c 1 CD11b 1 dDC2s 35 ), and all 3 subsets of cells have been implicated in CHS pathology. 36 In response to DNFB treatment alone, both Rubcn 1/1 and Rubcn -/ears contained equivalent levels of LCs, dDC1s, and dDC2s.…”
Section: Resultsmentioning
confidence: 99%
“…However, UV pretreatment did not inhibit recruitment of macrophages and neutrophils to DNFB-treated Rubcn -/ears, though mast cells were efficiently suppressed by UV exposure in Rubcn -/mice (Fig 3, A). In addition to ubiquitous immune cells, the skin contains specialized resident immune cells (such as CD207 1 CD11c 1 CD11b 1 LCs, CD103 1 CD207 1 CD11c 1 CD11b lo dDC1s and CD301b 1 CD207 lo CD11c 1 CD11b 1 dDC2s 35 ), and all 3 subsets of cells have been implicated in CHS pathology. 36 In response to DNFB treatment alone, both Rubcn 1/1 and Rubcn -/ears contained equivalent levels of LCs, dDC1s, and dDC2s.…”
Section: Resultsmentioning
confidence: 99%
“…Reports indicated that autophagy is necessary for skin pigmentation and melanin synthesis. In other words, in the autophagy disturbance in skin cells, cells undergo ageing, P53 upregulation, and ichthyosis . These findings were in good agreement with our data that showed acidic media enhanced autophagy and P53 downregulation in fibroblasts.…”
Section: Discussionsupporting
confidence: 93%
“…Several kinds of signaling mechanisms, including calcium ion concentration, retinoic acid receptor (RAR), and vitamin-D receptor signaling, are reported as regulating the differentiation of keratinocytes, and autophagy is also involved in the epidermal differentiation process [12]. It has also been reported that autophagy plays important roles in inflammation, the anti-oxidant system [20], and skin barrier formation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, autophagy signaling in skin, and its physiological roles in skin homeostasis, have been extensively investigated. Along with the crucial roles in epidermal differentiation process [12], potential involvement in skin barrier functions, inflammation [13], and even in the aging process [14] have been suggested for the autophagy process. Recently, we also reported that the topical application of the autophagy activating molecule significantly reduced the oxidative stress marker molecule, carbonylated proteins, in stratum corneum clinically [15].…”
Section: Introductionmentioning
confidence: 99%